HUBUNGAN POWER OTOT TUNGKAI DAN POWER OTOT LENGAN DAN BAHU DENGAN ACCURACY SMASH PADA TIM VOLI PUTRI MA DARUL QUR’AN - Muhammad Abror; Drs. Ramadi, M.Kes, AIFO '; Ardiah Juita, S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study originated from the observation that the writer found in the field, it turns out the students are less success in doing smash in practice, the results of unsatisfactory accuracy smash has not achieved good results, this is caused by the jump is too high therefore the ball cannot run dynamically. The factor that caused less success doing smash was lack of the element of physical condition named power. The purpose of this study was to determine the relationship of leg muscle power and arm and shoulder muscle power with accuracy smash results at female volley ball team of MA Darul Qur’an. The population in this study was 12 samples. The sampling technique in this study was total sampling for counting a sample that is not too large. Instruments of this research were vertical power jump test in order to measure the leg muscle power, then two-hand medicine ball put test in order to measure arm and shoulder muscle power and the last smash ability test in order to measure the accuracy smash. The results showed that there is a significant relationship with r table at α (0,05) = 0,576 while r count > r table, it means that hypothesis was received and there is a significant relationship of leg muscle power and arm and shoulder muscle power with accuracy smash at female volley ball team of MA Darul Qur’an.Key Words: Leg Muscle Power, Arm And Shoulder Muscle Power, Accuracy Smash